Report on the Outcome of the FATF Plenary Meeting and Proposal for the Endorsement of the Methodology for Assessing Compliance with Anti-Money Laundering and Combating the Financing of Terrorism Standard. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
NULL.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet